PENGARUH PARTISIPASI, KEJELASAN SASARAN, GROUP COHESIVENESS DAN INFORMASI ASIMETRI ANGGARAN TERHADAP BUDGETARY SLACK DI SELURUH KECAMATAN KOTA MEDAN - Anggi Pratama Nst; Misna Kiyah (Universitas Medan Area, 2019)
This study aims to analyze the effect of budgetary participation, clarity of budget targets, group cohesiveness, and asymmetric information on budgetary slack, and examine the effect of ethical considerations in moderating the relationship between budget participation, clarity of budget goals, group cohesiveness, and asymmetric information on budgetary slack. The total population sampled was 63 populations (location of all sub-district offices in the city of Medan). Based on the results of the study, all independent variables, namely budget participation, clarity of budget targets, group cohesiveness and asymmetric information simultaneously have a significant effect on budgetary slack. The results of the partial test, for the budget participation and asymmetry information did not significantly influence the budgetary slack, in contrast to the clarity of the budget target and cohesiveness group which partially had a significant effect on budgetary slack.